Effectiveness of Symbolic Communication Therapy on Expressive Abilities in Post- Stroke Aphasia - Evarina Sembiring; Flora Sijabat; Harold Situmorang; Amila Amila; Zuraidah Mastura Daulay; Dearni Trinitas Zebua (JKG (JURNAL KEPERAWATAN GLOBAL), 2025)
Background: Aphasia is a major post-stroke complication that causes communication difficulties and significantly reduces patients’ quality of life. Conventional speech therapy is often limited by time and resources, highlighting the need for technology-based alternatives that can be practiced independently at home. This study aimed to evaluate the effectiveness of a symbolic communication therapy (SCT) application in improving communication skills among stroke patients with aphasia. Methods: A one-group pretest–posttest quasi-experimental design was used with 15 motor-aphasia patients recruited from the Neurology Ward of Haji Medan General Hospital. Participants used an Android-based SCT application for six weeks (two 30-minute sessions per day). Functional communication ability was assessed using the Derby Functional Communication Scale (DFCS) before and after intervention. Data were analyzed using the Wilcoxon Signed-Rank Test. Results: The SCT application significantly improved patients’ communication performance. DFCS scores increased in expression (5.93 to 6.93), comprehension (5.47 to 7.93), and interaction (4.93 to 6.93) domains (p < 0.001). Conclusion: The SCT application effectively enhances functional communication in post-stroke aphasia patients and can serve as a complementary, low-cost tool within neurological rehabilitation programs, particularly in resource-limited healthcare settings.